Pendidikan Islam Dalam Menangani Tantangan Global - Mardiah Astuti; Herlina Herlina; Ibrahim Ibrahim; Yusniasari Yusniasari; Selpita Selpita; Mia Anisa; Indah Purnamasari (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
: This article is about Islamic education in dealing with global challenges. This is a very big challenge for Islamic education, because the amount and level of information cannot be filtered if the younger generation is accessing unlimited information. This research was conducted using two methods, namely qualitative research through questionnaires and literature studies by looking at previous studies whose theme is of course related to the title of this article.